Economic Development of Indigenous Communities In North Toraja Regency To Face The Digital Marketing Era, Through The Use of Fintech-Based Epayments And Payments - Kurniasari, Lisa; Yulian Pompeng, Olivia Devi (Devotion : Journal of Research and Community Service, 2022)
Promotions done by an endorser through social media like Instagram doesn't only use by companies big in activity marketing them, but also can use to promote a product from local MSME brands for increased sale product online. Based on the amount variables and indicators used in research _, the approach sample representative used in the withdrawal sample, so that amount is as many as 80 to 160 respondents. The purposive sampling technique that became part of the non-probability sampling technique will be used for determining the respondents who become the sample. During the research, a set of questionnaires with choice 5 Likert scale answers will be given to the target respondent as the primary data source. After the research data is obtained, the data then will analyze for the validity and reliability test. After the data is found to be valid and reliable, the method of partial least squares (PLS) analysis will use to test the proposed hypothesis. Analysis performed statistics _ includes evaluation of the outer and inner models. The expected results and outcomes of the research produce a reference for the perpetrators MSME business in To do activity businesses that use endorsers as one of the methods for strengthening brand attitude when consumers To do decision online purchases. Research results this is at TKT 2. Results obtained from the study will be published in Accredited National Journal: Journal of Business Economics, State University of Malang Accredited Sinta 4 with p-ISSN: 0853-7283 and e-ISSN: 2528-0503 as outside Mandatory accepted and Journal Management Marketing of Petra Christian University Accredited Sinta 3 with p-ISSN: 1907235X and e-ISSN: 1907235X as outside additions submitted. And the 2021 National Seminar on Management and Business Economics (SNMEB) as an outside Additional.